2023
DOI: 10.1002/adhm.202300905
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Bioprinting of Breast Tumor Cells and Organoids Using Low‐Concentration Collagen‐Based Bioinks

Wen Shi,
Sameer Mirza,
Mitchell Kuss
et al.

Abstract: Bioinks for 3D bioprinting of tumor models should not only meet printability requirements but also accurately maintain and support phenotypes of tumor surrounding cells to recapitulate key tumor hallmarks. Collagen is a major extracellular matrix protein for solid tumors, but low viscosity of collagen solution has made 3D bioprinted cancer models challenging. This work produces embedded, bioprinted breast cancer cells and tumor organoid models using low‐concentration collagen I based bioinks. The biocompatible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…36 Additionally, the gelatin hydrogel was introduced here mainly as an auxiliary phase to promote the extrusion printing of low-concentration collagen solutions, because low-concentration collagen solutions are commonly mechanically weak and have low viscosity, which makes the extrusion printing of a single collagen component very challenging. 37,38 On the other hand, the thermosensitive gelatin served as a sacrificial phase owing to its ability to liquefy at 37 °C post-printing. In the incubator, the sacrificial gelatin melted while the collagen gradually crosslinked, which synergistically facilitated the process of cell assembly within the GelMA bath.…”
Section: Resultsmentioning
confidence: 99%
“…36 Additionally, the gelatin hydrogel was introduced here mainly as an auxiliary phase to promote the extrusion printing of low-concentration collagen solutions, because low-concentration collagen solutions are commonly mechanically weak and have low viscosity, which makes the extrusion printing of a single collagen component very challenging. 37,38 On the other hand, the thermosensitive gelatin served as a sacrificial phase owing to its ability to liquefy at 37 °C post-printing. In the incubator, the sacrificial gelatin melted while the collagen gradually crosslinked, which synergistically facilitated the process of cell assembly within the GelMA bath.…”
Section: Resultsmentioning
confidence: 99%
“…Support bath materials are very helpful in preventing the collapse of printed three–dimensional complex structures. Several studies have reported the use of various synthetic materials such as Laponite, Carbopol, Pluronic F127 and natural materials like agarose, alginate, silk fibroin and gelatin in support bath systems to fabricate complex organs using extrusion–based bioprinting [ 36 , 49 , 54 , 57 , 59 , 142 ].…”
Section: Materials Used For Support Bath Preparationmentioning
confidence: 99%
“…Moreover, tumor organoids were developed by printing breast cancer cells in the core region and fibroblast cells in the peripheral region. Among the three bioinks (C, CH, M), CH bioink uniquely preserved the phenotypic characteristics of both epithelial tumor cells and fibroblasts due to their ability to replicate the in vivo breast cancer tumor microenvironment demonstrating the importance of extracellular matrix (ECM) components in the fidelity of tumor models [ 142 ]. In another study, Maloney et al, used embedded bioprinting technology to screen chemotherapeutic drugs for HepG2, Caco2, and patient–derived glioblastoma and sarcoma.…”
Section: Applications Of Embedded Bioprintingmentioning
confidence: 99%
“…The utilization of the Matrigel in 3D bioprinting of organoids remained relatively limited [24], with most studies opting for direct use of conventional bioinks for printing and culturing tumor organoids. However, this approach often failed to provide optimal growth conditions for the organoids, thereby compromising their viability during the cultivation process and influencing experimental outcomes [13,25]. In contrast, this work had developed a composite bioink that not only meets the requirements for excellent printability but also maximally preserves the activity of tumor organoids, thus enabling superior construction of in vitro models.…”
Section: D Bioprinting and Organoid Culture With The Composite Bioinkmentioning
confidence: 99%